Requiem for the Santa Cruz : An Environmental History of an Arizona River - Webb, Robert H.; Turner, R. M. (Raymond M.); Johnson, R. Roy (Raymond Roy), 1932-; Betancourt, Julio L. (Book collections on Project MUSE., 2014)
"Requiem for the Santa Cruz is the natural history of the life and death of a Southwestern river. The book is a model for explaining changes in river systems and the consequences"--